2023
DOI: 10.1021/acs.inorgchem.3c01428
|View full text |Cite
|
Sign up to set email alerts
|

AAl(Te4O10) (A = Na, Ag) and K2Ga2(HTe6O16)(HTeO3): Three Aluminum/Gallium Tellurites with Large Birefringence and Wide Band Gap

Abstract: The exploration of novel inorganic tellurites is significant because of their promising applications in nonlinear-optical materials and birefringent materials. Herein, three new aluminum/gallium tellurites, namely, NaAl(Te 4 O 10 ) (1), AgAl(Te 4 O 10 ) (2), and K 2 Ga 2 (HTe 6 O 16 )(HTeO 3 ) (3), have been successfully obtained by mild hydrothermal reactions. The isostructural compounds 1 and 2 contain the Te 3 O 8 trimer, while compound 3 contains an unprecedented Te 6 O 16 hexamer. Notably, all three compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…4b). It is worth noting that Pb 3 (TeO 3 )Br 4 exhibits a similar birefringence to those of previously reported Te oxides, such as Y 3 (TeO 3 ) 2 (SO 4 ) 2 (OH)(H 2 O) (0.092@532 nm), 15 AgAl(Te 4 O 10 ) (0.104@532 nm), 19 BaF 2 TeF 2 (OH) 2 (∼0.078@300–700 nm), 39 Rb[Te 2 O 4 (OH) 5 ] (0.0545@1064 nm), 58 Li 2 ZrTeO 6 (0.064@1064 nm) 59 and AgTeO 2 F (0.078@1064 nm). 52…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…4b). It is worth noting that Pb 3 (TeO 3 )Br 4 exhibits a similar birefringence to those of previously reported Te oxides, such as Y 3 (TeO 3 ) 2 (SO 4 ) 2 (OH)(H 2 O) (0.092@532 nm), 15 AgAl(Te 4 O 10 ) (0.104@532 nm), 19 BaF 2 TeF 2 (OH) 2 (∼0.078@300–700 nm), 39 Rb[Te 2 O 4 (OH) 5 ] (0.0545@1064 nm), 58 Li 2 ZrTeO 6 (0.064@1064 nm) 59 and AgTeO 2 F (0.078@1064 nm). 52…”
Section: Resultssupporting
confidence: 83%
“…11,18 and their derivatives (GaO 6 , GaO 3 F 3 , etc. ), [19][20][21] d 10 transition metals with large polar displacement (Zn 2+ , Cd 2+ , Hg 2+ ), 22,23 and SALP cations (Pb 2+ , Bi 3+ , Sn 2+ , Sb 3+ , etc.). 24,25 Some high-performance NLO materials have been explored, such as Pb 2 (SeO 3 )(NO 3 ) 2 (2 × KDP), 26 NaNbO(SeO 3 ) 2 (7.8 × KDP), 18 LiNbTeO 5 (17 × KDP), 27 Cd 2 Nb 2 Te 4 O 15 (31 × KDP), 28 β-BaTeW 2 O 9 (1.5 × KTP) 29 and TlSb 3 Te 2 O 12 (37.2 × KDP).…”
Section: Introductionmentioning
confidence: 99%
“…Exploring new material systems is of great importance, because it contributes to expand the chemical space and discovery novel materials with unique properties and potential applications. By investigating new inorganic compound systems, researchers can uncover unprecedented structural motifs, understand the relationships between structures and properties, and potentially develop advanced materials for various technological applications. Selenites have garnered the attention of scientists due to their unique physical and chemical properties. They possess stereochemically active lone-electron pairs, making them promising candidates of nonlinear optical (NLO) and birefringent materials . Over the past few decades, research on selenite compounds has identified over a thousand different chemical entities.…”
mentioning
confidence: 99%
“…13–17 To be commercially available, UV NLO materials need to simultaneously meet the following conditions: (a) a large second harmonic generation (SHG) response, (b) a wide band gap, (c) a high laser-induced damage threshold (LIDT), (d) high thermal stability and excellent environmental stability, and (e) sufficient birefringence to satisfy phase matching. 18–24 Due to the contradiction between the above conditions, it is very difficult to synthesize UV NLO materials with balanced properties. Therefore, how to design UV NLO materials with balanced performance is a very urgent task.…”
Section: Introductionmentioning
confidence: 99%